2017
DOI: 10.1002/pen.24518
|View full text |Cite
|
Sign up to set email alerts
|

Understanding surface discharge activity with epoxy silicon carbide nanocomposites

Abstract: Surface discharge inception voltage (SDIV) with epoxy silicon carbide nanocomposite material in LN 2 medium is about three times higher than that in air. Under AC voltage that SDIV increases with increase in wt% of silicon carbide (SIC) material in epoxy nanocomposites. Dielectric measurements indicates an increase in temperature of the specimen and the weight percentage of SIC filler in epoxy resin increases the permittivity of the material. Also, irrespective of percentage of SiC in epoxy resin, the tan(d) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Sarathi et al, have previously indicated that the decay rate of surface potential is nearly the same with epoxy silicon carbide nanocomposites. [ 29 ] The charge accumulated on an insulating material can dissipate in three different methods: (a) along the surface of the specimen, (b) into the bulk of the specimen, and (c) into the surrounding ambience. [ 30 ] The dissipation along the surface is mainly affected by surface resistivity of the material.…”
Section: Resultsmentioning
confidence: 99%
“…Sarathi et al, have previously indicated that the decay rate of surface potential is nearly the same with epoxy silicon carbide nanocomposites. [ 29 ] The charge accumulated on an insulating material can dissipate in three different methods: (a) along the surface of the specimen, (b) into the bulk of the specimen, and (c) into the surrounding ambience. [ 30 ] The dissipation along the surface is mainly affected by surface resistivity of the material.…”
Section: Resultsmentioning
confidence: 99%
“…The aforementioned interpretations seem to be in agreement with [9], where it was reported that there can be surface modifications of the nanocomposites and of the nature of the interface in the region around the nanofillers. These views are also shared in [10,11]. It is true that the present research was carried out using AC voltages whereas it is intended that the tested materials will be used for DC transmission.…”
Section: Flashover Voltages For Various Droplet Arrangements On Xlpe Surfaces With Added Mgo Nanofillersmentioning
confidence: 89%
“…The voltage at which UHF sensor generates UHF signal, on the application of voltage, is defined as CIV [16,20]. It is observed from Fig.…”
Section: Water Droplet Initiated Discharge Studiesmentioning
confidence: 99%
“…Also, the water droplet on insulation material formed due to rain or fog condensation during power apparatus operation may lead to the formation of the corona and further leads to surface discharge activity due to enhancement in the local field. Sarathi et al [16] have studied water droplet initiated corona discharges under different voltage profiles through radiated UHF signals. The discharges caused due to water droplet reduce the hydrophobicity of the material and formation of carbonised marking on the surface of the material, which further reduce the lifetime and cause the failure of insulation structure.…”
Section: Introductionmentioning
confidence: 99%